An Immobilization Technique for Long-Term Time-Lapse Imaging of Explanted Drosophila Tissues - Bostock, Matthew P.; Prasad, Anadika R.; Chaouni, Rita; Yuen, Alice C.; Sousa-Nunes, Rita; Amoyel, Marc; Fernandes, Vilaiwan M. (Frontiers in Cell and Developmental Biology, 2020)
Time-lapse imaging is an essential tool to study dynamic biological processes that cannot be discerned from fixed samples alone. However, imaging cell-and tissue-level processes in intact animals poses numerous challenges if the organism is opaque and/or motile. Explant cultures of intact tissues circumvent some of these challenges, but sample drift remains a considerable obstacle. We employed a simple yet effective technique to immobilize tissues in medium-bathed agarose. We applied this technique to study multiple Drosophila tissues from first-instar larvae to adult stages in various orientations and with no evidence of anisotropic pressure or stress damage. Using this method, we were able to image fine features for up to 18 hours and make novel observations. Specifically, we report that fibers characteristic of quiescent neuroblasts are inherited by their basal daughters during reactivation; that the lamina in the developing visual system is assembled roughly 2-3 columns at a time; that lamina glia positions are dynamic during development; and that the nuclear envelopes of adult testis cyst stem cells do not break down completely during mitosis. In all, we demonstrate that our protocol is wellsuited for tissue immobilization and long-term live imaging, enabling new insights into tissue and cell dynamics in Drosophila.